2013
DOI: 10.1016/j.euromechsol.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A homogenization approach for assessing the yield strength properties of stone column reinforced soils

Abstract: International audienceThe macroscopic strength properties of a purely cohesive soil reinforced by a periodic distribution of "stone columns" made of a highly frictional granular material are investigated in a rigorous way on the basis of the yield design homogenization approach. Starting from a first crude lower bound approximation to the macroscopic strength criterion of the stone column reinforced soil, a much more accurate failure surface is then drawn in the space of stresses as a result of a series of num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…Even though it allows to have more information than the method presented here (namely along the stress path during the loading increase), this procedure may quickly become slow and tedious, because many increments are necessary to capture the limit load. Authors have made such calculations with a similar computer and commercial finite element code, with von Mises and Drucker-Prager materials, which have taken several days with the same discretization of the stress space [22]. With a dedicated homemade finite element code, which permits to treat Tresca and MohrCoulomb materials in an elastoplastic procedure, the so-obtained macroscopic strength domain is in quite good agreement with the present results.…”
Section: Lower and Upper Bound Estimates For The Macroscopic Strengthsupporting
confidence: 83%
“…Even though it allows to have more information than the method presented here (namely along the stress path during the loading increase), this procedure may quickly become slow and tedious, because many increments are necessary to capture the limit load. Authors have made such calculations with a similar computer and commercial finite element code, with von Mises and Drucker-Prager materials, which have taken several days with the same discretization of the stress space [22]. With a dedicated homemade finite element code, which permits to treat Tresca and MohrCoulomb materials in an elastoplastic procedure, the so-obtained macroscopic strength domain is in quite good agreement with the present results.…”
Section: Lower and Upper Bound Estimates For The Macroscopic Strengthsupporting
confidence: 83%
“…This intuitive idea is fully and rigorously confirmed by the homogenization method developed in the context of the yield design theory for reinforced soils in general and column‐reinforced soils in particular . It has thus been shown that a purely cohesive soil reinforced by purely cohesive inclusions (‘lime columns’ technique) may be perceived as a homogenous but anisotropic purely cohesive medium.…”
Section: Introductionmentioning
confidence: 99%
“…The recent improvement of numerical methods has allowed to get an accurate knowledge of the macroscopic failure behaviour of stone column reinforced soils [20,34]. But the implementation of such a macroscopic strength domain in order to analyze the stability of homogenized equivalent structures remains so far quite inexistent for such reinforced soils [35].…”
Section: The Yield Design Homogenization Approachmentioning
confidence: 99%
“…where the first four equations refer to the static admissibility in the context of periodicity (see [20] for more details). The respect of the local strength criterion is expressed by the last condition.…”
Section: Static and Kinematic Approaches Applied To The Auxiliary Promentioning
confidence: 99%
See 1 more Smart Citation